2007
DOI: 10.1007/s00595-007-3548-y
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Micrometastasis: A Predictor of Early Tumor Relapse After Complete Resection of Histologically Node-Negative Esophageal Cancer

Abstract: The prevalence of LNMM in patients with pN0 ESCC was 34.4% (32/93). Thus, LNMM was significantly associated with the disease-free interval. T status and LNMM were both independent prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 11 publications
0
25
1
Order By: Relevance
“…Follow-up studies consisted of physical examination, laboratory analysis, barium esophagram, ultrasound examination, computed tomography and fiberoptic esophagoscopy to detect recurrent diseases (Li et al 2007). Followup was completed in all 157 patients until May 2011, and the median follow-up period was 39 months (range: 6-73 months).…”
Section: Patients and Follow-upmentioning
confidence: 99%
“…Follow-up studies consisted of physical examination, laboratory analysis, barium esophagram, ultrasound examination, computed tomography and fiberoptic esophagoscopy to detect recurrent diseases (Li et al 2007). Followup was completed in all 157 patients until May 2011, and the median follow-up period was 39 months (range: 6-73 months).…”
Section: Patients and Follow-upmentioning
confidence: 99%
“…Li et al present similar observations. The author observed the appearance of micrometastases in 9.4% of examined lymph nodes but together with the feature T they constitute an independent prognostic factor in the overall 5-year survival rate of the patients [21]. Some authors point out that hidden micrometastasis should be defined as every metastasis found in classic microscopic study [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] On the other hand, many reports have indicated that immunohistochemical nodal micrometastasis is a significant prognostic indicator in patients with cN0 esophageal cancer. [31][32][33] Although SN mapping in esophageal cancer is obviously more invasive than other imaging techniques, nodal micrometastasis in SN that may affect survival of the patient cannot be ignored. At present, SN biopsy is believed to detect micrometastasis more accurately and cost-effectively than other imaging procedures in patients with cN0 early esophageal cancer.…”
Section: Micrometastasis In Sentinel Nodes Of Patients With Early Esomentioning
confidence: 99%